O desenho de cursos por competências como possibilidade de intervenção interdisciplinar nas qualificações profissionais - Domingues, Rosiris Maturo (2015)
This study aimed to investigate the possibilities of the courses design of the Professional Qualification of Senac São Paulo, as contribution to an interdisciplinary teaching practice, also funding an analysis of the formal curriculum and held curriculum. It were considered the most recent transformations at the national level, with regard to education and the history of the institution, revealing concepts as resume, skills, and interdisciplinary work to answer if the courses design developed by skills enables or hinders the pedagogical practice in an interdisciplinary perspective. It was a qualitative research and interdisciplinary intervention that involved participatory research, the narrative of the experiences and life story written under the metaphor of resource. Interdisciplinary as analysis, since maintained continuous dialogue with and among the authors involved in the issue. The main results it was found that the design of courses under the curriculum paradigm skills, brings possibilities for interdisciplinary intervention to the extent this paradigm, similar to interdisciplinary assumptions, and based on the design of integral education of the individual. However, considering the interdisciplinarity as a category of action, which takes place in the act of teaching and the multiple and complex relationships in the classroom, the interdisciplinary intervention cannot do without, necessarily prescribed guidelines in curriculum planning; it lacks articulation and commitment from / to all school stakeholders with thinking and interdisciplinary and teaching posture, the assumption of their professionalism, these assumptions giving rise to a formation, also interdisciplinary